2017
DOI: 10.1161/strokeaha.116.015890
|View full text |Cite
|
Sign up to set email alerts
|

Specific Lobar Affection Reveals a Rostrocaudal Gradient in Functional Outcome in Spontaneous Intracerebral Hemorrhage

Abstract: Between 2008 and 2012, all consecutive patients with atraumatic ICH admitted to the Department of Neurology of the university hospital Background and Purpose-Several studies have reported a better functional outcome in lobar intracerebral hemorrhage (ICH) compared with deep location. However, among lobar ICH, a correlation of hemorrhage site-involving the specific lobes-with functional outcome has not been established. Methods-Conservatively treated patients with supratentorial ICH, admitted to our hospital ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…This is of importance, as several recent studies have shown that particular locations within the lobes of the brain and thalamus have differing influence on clinical outcome. 25,26 In conclusion, we showed that haemorrhage location can predict haematoma expansion and clinical outcome in spontaneous ICH. In particular, we found that lobar ICH was associated with significant haematoma expansion and poor outcome.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This is of importance, as several recent studies have shown that particular locations within the lobes of the brain and thalamus have differing influence on clinical outcome. 25,26 In conclusion, we showed that haemorrhage location can predict haematoma expansion and clinical outcome in spontaneous ICH. In particular, we found that lobar ICH was associated with significant haematoma expansion and poor outcome.…”
Section: Discussionmentioning
confidence: 61%
“…This is of importance, as several recent studies have shown that particular locations within the lobes of the brain and thalamus have differing influence on clinical outcome. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma location and volume, the presence of the intraventricular extension (16), BHS (21), BS (20), island sign (23), and satellite sign (22) was assessed. Hematoma location was divided into deep, lobar, brain stem, and cerebellum (24), and deep ICH was defined as hematoma involving the thalamus or basal ganglia. Baseline hematoma volume was divided into four categories: <10, 10-20, 20-30, and ≥30 ml.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…In this retrospective study, the prevalence of occipital ICH was The prevalence and volume of occipital ICH in our study are equal to the findings of Gerner et al who discovered occipital location to be the rarest, even when adjusted for the size of the lobes. 11 The infrequency is even more pronounced considering that the occipital lobe is the preferred location of amyloid angiopathy. 16 Moreover, they reported that the occipital lobe harbored the smallest hematoma with the least growth, 11 which was hypothesized to stem from a higher gray/white-matter (GW) ratio 17 and lower arterial pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar topological data on hemorrhage are scarce. In one study, isolated occipital hemorrhages were rare (4.6% of lobar ICH) and had better outcome than other lobar hemorrhages, 11 whereas another study did not find any occipital areas associating with lower acute mortality 12 …”
Section: Introductionmentioning
confidence: 99%